The importance of referral in specifying effectualmess of grammatical structure - سلطــــــان ميس; عبد الحميد وقاف (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
referral is a terme releted to signs i. e every thing that would reffer to a sensory or moral reference. signs form an important part of linguistics scinnces, specifically grammar. sign names, pronouns, and relative nouns form an impotant part of the grammatical study, which is mainly based on defining the grammatical relationships that link structures. these relationships are affected by referral, which includes the pronouns of the speaker, the interlocutor, and the absent these pronouns can be visible or implicit what shows this influence in particular is the context of pronunciation, because it is what determines the reference of signs and from which they take their specificity.